The Financial Behaviour in VUCA Era: A Literature Study - Angreyani, Andi Dewi; Yusuf, Marwah (Jurnal Riset Bisnis, Manajemen, dan Ilmu Ekonomi, 2025)
The concept of volatility, uncertainty, complexity, and ambiguity (VUCA) has emerged as a critical framework for understanding contemporary financial behavior. This literature study synthesizes existing research to elucidate how VUCA conditions influence financial decision-making among individuals and organizations. Despite the growing relevance of VUCA, there is a stark gap in how financial models adapt to these unpredictable environments, which traditional theories often overlook. Through a qualitative meta-analysis of peer-reviewed articles, this study reveals that cognitive biases become amplified in VUCA contexts, leading to irrational financial behaviors. Key findings indicate that stakeholders who embrace adaptive strategies—such as diversified portfolios and flexible financial models—are more likely to navigate the complexities of VUCA successfully. Additionally, advancements in technology provide opportunities for informed decision-making, albeit introducing challenges like information overload. This study concludes by highlighting the need for interdisciplinary approaches to further investigate financial behavior across varied demographics and suggests that integrating VUCA awareness into financial education may enhance decision outcomes in unstable environments. Future research should focus on the evolving interplay between behavioral finance and technology to develop more robust financial strategies. Konsep volatilitas, ketidakpastian, kompleksitas, dan ambiguitas (VUCA) telah muncul sebagai kerangka kerja kritis untuk memahami perilaku keuangan kontemporer. Studi literatur ini menyintesis penelitian yang ada untuk menjelaskan bagaimana kondisi VUCA memengaruhi pengambilan keputusan keuangan di kalangan individu dan organisasi. Meskipun relevansi VUCA semakin meningkat, terdapat kesenjangan yang mencolok dalam cara model keuangan beradaptasi dengan lingkungan yang tidak dapat diprediksi ini, yang sering diabaikan oleh teori-teori tradisional. Melalui meta-analisis kualitatif artikel yang telah diulas melalui pendekatan peer-review, studi ini mengungkapkan bahwa bias kognitif menjadi lebih menonjol dalam konteks VUCA, yang mengakibatkan perilaku keuangan irasional. Temuan utama menunjukkan bahwa pemangku kepentingan yang mengadopsi strategi adaptif—seperti portofolio dan model keuangan yang fleksibel—lebih mungkin berhasil menavigasi kompleksitas VUCA. Selain itu, kemajuan teknologi memberikan peluang untuk pengambilan keputusan, meskipun juga menimbulkan tantangan seperti kelebihan informasi. Studi ini menyimpulkan dengan menekankan perlunya pendekatan interdisiplin untuk menyelidiki lebih lanjut perilaku keuangan di berbagai demografi dan menyarankan bahwa integrasi kesadaran VUCA ke dalam pendidikan keuangan dapat meningkatkan hasil keputusan dalam lingkungan yang tidak stabil. Penelitian masa depan harus fokus pada interaksi yang terus berkembang antara keuangan perilaku dan teknologi untuk mengembangkan strategi keuangan yang lebih tangguh.